Does access to ICTs equally matter for men and women in terms of academic exam performance? The case of middle education in Colombia - Jorge Leonardo Rodríguez Arenas; Luis Fernando Gamboa (Revista de Economía del Rosario)
This paper analyzes the impact of Information and Communication Technologies (ICT) on the academic performance of students in Colombia, specifically in mathematics and reading. Using data from secondary school students between 2017 and 2019, ICT access is measured through the availability of computers and Internet. The results indicate that access to ict improves mathematics scores by 0.068 standard deviations, while no significant effect is observed in reading. Additionally, having a computer without Internet access does not affect scores. These findings provide relevant insights for policies aimed at reducing the digital divide. No differential effects are found between males and females.